The effect of the cooperative learning model on basketball games to improve junior high school students' learning - Ridwan Afif; Carles Nyoman Wali; Pamuji Sukoco (Journal Sport Area, 2022)
This research is motivated by the low value of student participation in the learning process of the basketball game, while another problem is that the model used by the teacher is not appropriate. Learning outcomes of junior high school students and to determine the effectiveness of the cooperative learning model of basketball learning in improving basketball learning outcomes of junior high school students. The type of method in this research is quasi-experimental. The instruments used to collect data are questionnaires, student assessment rubrics, and observations. The design in this research is One Group Pretest-Posttest Design. Data collection techniques in this study are interviews, preliminary research and offline questionnaire distribution. The place in this research is SMP Muhammadiyah 2 Yogyakarta. Data analysis in this study is tested using t-test which includes hypothesis testing, homogeneity test, and normality test. The results of this study indicate that there is an effect of the cooperative learning model on improving the learning outcomes of junior high school students about the game of basketball. Thus the hypothesis in the study is accepted.